Product Quality of Quercetin Extract From Carica Papaya L Flower by Microwave-Assisted Extraction (MAE) - Mukhaimin, Iman; Saraswati, Enggar Ayu; Ajizah, Rahma; Triyastuti, Meilya Suzan (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2019)
These work aims are to determine the best condition extraction and product quality of quercetin from Carica papaya L flowers extract. The extraction of quercetin from Carica papaya L flowers had done by microwave-assisted extraction (MAE) method. Dried flowers prepared by cutting into 0,125 mm of particle size. Dried flowers were extracted using methanol 80% (w/w) to determine influence of solid to liquid, S/L, ratio (1:10, 1:15, 1:20), microwave power (120, 200, 280, 400 W), and extraction time (1-5 minutes) on extraction process. Using the phytochemical test by Mg-HCl-amyl alcohol and UV-Vis spectrophotometer techniques, the quercetin detected by qualitative and quantitative analysis. As a result, the presence of flavonoids detected by the formation of a brownish red-colored flavylium compound. Increasing extraction time, power, and S/L ratio increased the extraction temperature. Consequently, yield quercetin decreased when the temperature extraction exceeds its temperature degradation. The highest quercetin yield, 0.214%, was detected with solid to liquid ratio (1:15), microwave power (400 Watt), and extraction time (4 minutes). FTIR spectrophotometer technique on the highest yield quercetin proved that have product quality with 91,17% similarity on group function like OH, C=O, C=C, and C-H with quercetin standard spectrum.